Optional Word Order in Wh-Questions in Two Norwegian Dialects: A Diachronic Analysis of Synchronic Variation - Westergaard, Marit (Nordic Journal of Linguistics, 2005)
Based on a corpus of spontaneous production data, this paper compares the word order of wh-questions in two Norwegian dialects, Kåfjord and Tromsø. While the choice of word order (V2 or non-V2) in Tromsø is dependent on information structure, the Kåfjord speakers produce considerably more non-V2 in questions with monosyllabic wh-elements. The majority of questions with multisyllabic wh-constituents, on the other hand, occurs with V2. This synchronic variation is given a diachronic analysis within a Split-CP model of clause structure and a cue-based approach to acquisition and change, where an economy principle (head preference) also plays an important role. Furthermore, an information structure drift from V2 to non-V2 is argued to cause the cue for verb movement to fall below a critical level in the input to children, the result being that V2 only survives in lexically marked cases in Kåfjord, i.e. with the verb ‘be’.